THE IMMERSIVE METAVERSE PLAYBOOK FOR BUSINESS LEADERS a guide to strategic decision-making and implementation in the metaverse for improved products and services - Cronin, Irena; Scoble, Robert (Packt Publishing Ltd., 2023)
Discover what the metaverse can do for your business by exploring AR and VR, core support technologies, and use cases, while developing an understanding of its benefits, dangers, and future Key Features Understand the metaverse and learn how augmented reality and virtual reality are integral to it Get a solid understanding of core metaverse technologies Become a metaverse business thought leader by learning from real-world use cases Purchase of the print or Kindle book includes a free PDF eBook Book Description "The metaverse" has become a widely known term within a very short time span. The Immersive Metaverse Playbook for Business Leaders explicitly explains what it really refers to and shows you how to plot your business road map using the metaverse. This book helps you understand the concept of the metaverse, along with the implementation of generative AI in it. You'll not only get to grips with the underlying concepts, but also take a closer look at key technologies that power the metaverse, enabling you to plan your business road map. The chapters include use cases on social interaction, work, entertainment, art, and shopping to help you make better decisions when it comes to metaverse product and service development. You'll also explore the overall societal benefits and dangers related to issues such as privacy encroachment, technology addiction, and sluggishness. The concluding chapters discuss the future of AR and VR roles in the metaverse and the metaverse as a whole to enable you to make long-term business plans. By the end of this book, you'll be able to successfully invest, build, and market metaverse products and services that set you apart as a progressive technology leader. What you will learn Get to grips with the concept of the metaverse, its origin, and its present state Understand how AR and VR strategically fit into the metaverse Delve into core technologies that power the metaverse Dig into use cases that enable finer strategic decision-making Understand the benefits and possible dangers of the metaverse Plan further ahead by understanding the future of the metaverse Who this book is for If you are a C-suite technology and business executive, this book is for you. Investors, entrepreneurs, and other tech professionals will also find it beneficial. This book does not require any previous understanding of the metaverse or immersive technologies.
Keywords: Industrial management -- Technological innovations; Augmented reality -- Industrial applications; Virtual reality -- Industrial applications